Frequency dependence of the Isinghysteresis phasediagram: Mean field analysis - Punya A. (2014)
In this study, the magnetic hysteresis properties of the Ising model in an oscillating external magnetic field were evaluated using mean field analysis. The average magnetization over a full oscillating field-cycle, as a function of the field amplitude, field frequencies and temperature, was investigated. The dynamic phase transition boundaries between the dynamic ferromagnetic and paramagnetic phases were defined on the field amplitude and temperature plane for each field frequency, in order to study the effect of frequency on the hysteresis dynamic phase transition. For the results, the hysteresis behaviors across the dynamic phase transition boundary were observed using varying field frequencies. The frequency dispersion of the hysteresis area, the remanence and the coercivity were categorized into three distinct types. These phenomena can be explained through an understanding of the role of frequency in the alteration of the dynamic phase boundaries, something which results in anomalous hysteresis properties as a function of frequency. © 2010 Elsevier B.V. All rights reserved.